The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1257/aer.102.7.3594
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Foreign Ownership

Abstract: This paper uses a rich panel dataset of Spanish manufacturing firms (1990–2006) and a propensity score reweighting estimator to show that multinational firms acquire the most productive domestic firms, which, on acquisition, conduct more product and process innovation (simultaneously adopting new machines and organizational practices) and adopt foreign technologies, leading to higher productivity. We propose a model of endogenous selection and innovation in heterogeneous firms that explains both the observed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
96
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(137 citation statements)
references
References 41 publications
9
96
1
Order By: Relevance
“…However, it doesn't means that the reaction has reached to the "Pareto Optimal State", especially when it comes to the sustainable development of the enterprises. And as is known to all, the real estate industry will not be prosperous all the time, once the financial crisis break out again, it must endanger the subsistence and development of the firms [2]. In short, it can effectively provide the firms with the reference frame to research the impact of the house price on the firm innovation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it doesn't means that the reaction has reached to the "Pareto Optimal State", especially when it comes to the sustainable development of the enterprises. And as is known to all, the real estate industry will not be prosperous all the time, once the financial crisis break out again, it must endanger the subsistence and development of the firms [2]. In short, it can effectively provide the firms with the reference frame to research the impact of the house price on the firm innovation.…”
Section: Introductionmentioning
confidence: 99%
“…However, in their empirical approach they cannot claim to establish causal relationships. Another related paper is Guadalupe et al (2012), who investigate the link between foreign acquisition and innovation activity using firm level data for Spain. They also use a propensity score reweighting estimator, though not a doubly-robust estimator.…”
mentioning
confidence: 99%
“…Harris and Robinson (2002), Benfratello and Sembenelli (2006), Chen (2011), Balsvik and Haller (2010) and Guadalupe et al (2010) have previously shown that foreign MNEs are more likely to select domestic firms that are more productive, larger and more likely to conduct R&D. We build on that analysis to include the knowledge inputs used by firms. There also exists from Veugelers and Cassiman (2004), Criscuolo et al (2010) and Wagner (2006) cross-sectional evidence of differences in the type of knowledge inputs used by MNEs and non-MNEs.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Bandick et al (2010) and Bertrand (2009) find that R&D expenditures rose following foreign acquisition, while Stiebale and Reize (2011) report they fell. More recently Guadalupe et al (2010) have shown that the type of innovation (product or process) as well as other firm investments, including efforts to assimilate foreign technologies and purchases of new machinery and organisation practices, change in the post-acquisition period. Our evidence contributes to this literature by offering a more disaggregated study of the effects of acquisition FDI on R&D and in so doing sheds some light onto why the post-acquisition improvement in productivity in the target firm might occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation